SUBPOPULATIONS OF T LYMPHOCYTES IN THE ALLERGY IMMUNOPATHOGENESIS IN CHILDREN: A NEW IN THE FAMILIAR - V.V. Troshina; A.D. Pertseva (Union of pediatricians of Russia, 2011)
At present time few subpopulations T lymphocytes responsible for the implementation of various immune functions including regulatory have been described:Th1, Th2, Th17, Th3, Tr и Treg. As for the regulatory T lymphocytes (Treg), then the most convincingly established fact is their suppressing activity only for a single molecule - the transcription factor FOXP3+. The basis of representation of Treg participation in allergic processes - the presence of allergic manifestations in carriers of gene mutations FOXP3 - children with IPEX-syndrome. Elevated levels of CD4+CD25+-cells was also revealed in atopic dermatitis, contact dermatitis, and exacerbation of atopic form of bronchial asthma in children allergic to cow's milk lactalbumin. There is strong evidence of functional Treg impairment in allergies in children and restoration of their activity correlated with a positive effect of treatment. Approaches to the restoration of Treg function in allergic diseases in children are now actively being developed in the applied immunology. Key words: regulatory T lymphocyte subpopulations, immunopathogenesis, allergies, children. (Pediatric pharmacology. - 2011; 8 (6): 36-39)